2018
DOI: 10.3386/w25355
|View full text |Cite
|
Sign up to set email alerts
|

Racial Bias and In-group Bias in Judicial Decisions: Evidence from Virtual Reality Courtrooms

Abstract: We shot videos of criminal trials using 3D Virtual Reality (VR) technology, prosecuted by actual prosecutors and defended by actual defense attorneys in an actual courtroom. This is the first paper that utilizes VR technology in a non-computer animated setting, which allows us to replace white defendants in the courtroom with individuals who have Middle Eastern or North African descent in a real-life environment. We alter only the race of the defendants in these trials, holding all activity in the courtroom co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The advantage of West (2018) is he has objective information on whether certain citations were merited, which is not possible for use of force. In addition, this paper also complements research on racial bias in the criminal justice system more generally, including racial bias by prosecutors (Rehavi and Starr 2014, Sloan 2019, Tuttle 2019, juries (Anwar, Bayer, and Hjalmarsson 2012;Flanagan 2018) and judges (Arnold, Dobbie, and Yang 2018;Bielen, Marneffe, and Mocan 2018). 2 A second contribution of our paper is to demonstrate how the 911 call dispatch system can be used to assess the performance of individual officers, as well as for officers grouped by characteristics such as race.…”
mentioning
confidence: 89%
“…The advantage of West (2018) is he has objective information on whether certain citations were merited, which is not possible for use of force. In addition, this paper also complements research on racial bias in the criminal justice system more generally, including racial bias by prosecutors (Rehavi and Starr 2014, Sloan 2019, Tuttle 2019, juries (Anwar, Bayer, and Hjalmarsson 2012;Flanagan 2018) and judges (Arnold, Dobbie, and Yang 2018;Bielen, Marneffe, and Mocan 2018). 2 A second contribution of our paper is to demonstrate how the 911 call dispatch system can be used to assess the performance of individual officers, as well as for officers grouped by characteristics such as race.…”
mentioning
confidence: 89%
“…For example, Dotsch and Wigboldus (2008) found that people kept a farther distance when interacting with a virtual agent representing an outgroup member and displayed stronger negative association in implicit association tests used to measure implicit bias. In virtual courtrooms, participants were more likely to convict racial minority suspects to harsher punishments compared with White suspects (Bielen et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is possible to provide lived experiences through VR, which can enhance awareness and lead to attitudinal change (Friedman, 2005;Beadle and Santy, 2008;Li et al, 2011;Kandaurova and Lee, 2019). These applications often align with the broader objective of tackling discrimination and promoting diversity; and researchers have utilized VR to address gender and racial bias and to encourage social inclusion (Beadle and Santy, 2008;Bielen et al, 2018;Lopez et al, 2019). Specifically, studies have found that virtual embodiment of white people in a black virtual body is associated with an immediate decrease in implicit racial bias (Banakou et al, 2016).…”
Section: Application Of Digital Technologies (Vr Within and Beyond The Sport Industry)mentioning
confidence: 99%
“…We propose that, as a technological innovation, VR delivered through diversity training in sport organizations or used as a recruitment tool to engage the participation of disabled persons, could increase empathy toward persons with a disability, decrease social ableism (of and in persons with a disability), and therefore foster greater social inclusion in sport organizations. VR has been proven as a powerful mechanism used to tackle discrimination, promote diversity, and encourage attitudinal change (Beadle and Santy, 2008;Bielen et al, 2018;Lopez et al, 2019) but has yet to be applied in the context of sport, as an innovative approach to achieve a social inclusion legacy.…”
Section: Introductionmentioning
confidence: 99%